The Process of Variation That Goes on in Common Species - Gaibnazarova Feruza Pardabaevna; Safarova Nargiza Kamalovna (Genius Publishing Group, 2023)
The work is devoted to the study of the faunal spectrum of terrestrial mollusks of Uzbekistan and adjacent territories. The diversity of land mollusk species of Central Asia and the large number of endemic species sharply differs from other regions, and the process of formation of species continues intensively even now. It should be emphasized that variability is important in the process of formation of species. In general, we can find two different types of variability in the fauna of Central Asia. First of all, phenotypic variability is the manifestation of adaptation of molluscs to certain conditions to one degree or another
Keywords: malacofauna; mountain ranges; faunal spectrum; genus